Motion Range Event Detection Method on Application of Genesis Detection System on Volcanic Visual Monitoring - Rio Arie Purnama; Sukir Maryanto; Didik R. Santoso (Natural B, Journal of Health and Environmental Sciences, 2012)
The process of volcano research through visual monitoring usually takes a long time. There is many time possibility of an occurance of a specific volcano phenomena such as lava and plum. The problem with this monitoring activity can be helped through visual monitoring system that enables constant recording and automatically detects events that can be observed through the visual volcano object. This monitoring system works through an event detection application with static object definitive, fixed focus definitive and sensing area definitive combination method that forms a simple yet effective method called Motion Range Event Detection. This method is a form of volcano object monitoring using camera sensors by defining the form of volcano object as a static object and defining the object phenomena changes based on a predetermined area.